THEORETICAL FOUNDATIONS OF LINGUISTIC STUDY OF SOCIAL NETWORK LANGUAGE (Scientific journal of the Fergana State University, 2026)
This article analyzes the linguistic features of social media language in modern society and explores theoretical approaches to its study. Communication on platforms such as Facebook, Instagram, Twitter, and Telegram is characterized by brevity, informality, visual integration, interactivity, and the active use of neologisms. The study highlights analytical frameworks including sociolinguistics, discourse analysis, pragmatics, computer-mediated communication (CMC), and corpus linguistics. Examples of communication in Uzbek on Facebook, Instagram, and Telegram illustrate the specific features of virtual discourse in the Uzbek linguocultural context.